(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The editors-in-chief, editors, members of the editorial board and publisher of Epidemiology, Biostatistics and Public Health wish to express their sincere gratitude to the referees of the articles considered for the 2013 volume of the Journal. Giuseppe Arbia Fabio Barbone Joana Bastos Stefania Boccia Anna Bossi Silvio Brusaferro Chiara Cadeddu Caterina Caminiti Giovanni Capelli Guido Citoni Gianfranco Damiani Antonio De Belvis Emma De Feo Elisabetta De Vito Chiara de Waure Domitilla Di Thiene Ana Duarte Bruno Federico Monica Ferraroni Alessandra Frustaci Carlotta Galeone Silvano Gallus Maurizio Genuardi Guglielmo Giraldi Maria Rosaria Gualano Carolina Ianuale Farhad Islami Giuseppe La Torre Patrizia Laurenti Laura Lauria Carlo La Vecchia Emanuele Leoncini Alice Mannocci Walter Mazzucco Silvia Miccoli Cristina Montomoli Eva Negri Nicola Nicolotti Caterina Palazzo GianCarlo Paradisi Patrizio Pasqualetti Claudio Pelucchi Brunella Posteraro Delphine Praud Gianluigi Quaranta Luca Sbrogiò Benedetto Simone Giuliana Solinas Maria Lucia Specchia Annamaria Tortorano Fabio Turone Brigid Unim Maria Assunta Veneziano Francesco Vitale Antonella Zambon Alessandro Zanetti.